Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe CIRC (Cooperative Integrated Reading and Composition) terhadap Kemampuan Pemecahan Masalah Soal Matematika Siswa Kelas VIII SMP Negeri 2 Bengkalis - Muhammad Fahmi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
This research aim to to know there is or do not it him difference of ability of trouble-shooting between class using type cooperative model of CIRC (Cooperative Integreted Reading Composition and) at class student of VIII SMP Country 2 Bengkalis District Of Bengkalis Sub-Province of Bengkalis, and difference of[is make-up of ability of trouble-shooting. In research of its problem formula